RENEWAL OF THE EMPLOYMENT CONTRACT OF HONORARY EMPLOYEES IN BATAM CITY DEPARTMENT OF TRANSPORTATION BASED ON LAW OF THE REPUBLIC OF INDONESIA NO. 11 OF 2020 ON JOB CREATION - Oryza Sativa MY; David Tan (Universitas Internasional Batam, 2022)
Legal protection of workers is a guarantee of basic rights inherent and protected by law. Human rights are basic rights that must be protected. The legislation related to protection for workers is the Employment Cluster of Law No. 11 of 2020 on Job Creation. Honoree employees in the Batam Department of Transportation entered into a certain time work agreement (PKWT). Contract workers are legally defined as workers with a certain time status based on an agreement between the worker and the employer. Based on the title, topic, and background of the problem, the author made updates and improvements related to the employment contract of honorary employees (PKWT) of the Batam City Department of Transportation in the form of making employment documents. The renewal and improvement of the employment contract covers the duties and responsibilities of workers, workers' rights and obligations, salary payments and deductions, sanctions and compensation as well as the appointment and termination of employment (PHK) based on Employment Cluster of Law No. 11 of 2020 on Job Creation.